PROFILE OF VIEWERS OF FISHERIES BASED TELEVISION PROGRAMMES IN WEST BENGAL - Ghosh, Amitava; Sharma, Arpita; Das, S. K.; Sharma, Rama; Mishra, S. K. (Journal of Indian Fisheries Association, 2014)
Television is an effective medium for communication. In West Bengal, public television channel, i.e., Doordarshan Bangla is telecasted from Doordarshan Kendra, Kolkata. Some private television channels like ETV Bangla also started programmes like Annadata in W.B. and other state in regional languages. There is not much information available in literature about the profile of viewers of these programmes. Accordingly, a study was undertaken to explore this. Out of 19 districts of West Bengal, North 24-Parganas and South 24-Parganas districts were considered as locale of study. A total of 120 viewers covering 6 blocks of these two districts were interviewed to collect socio-economic and communication profile. Various variables indicating socio-economic and communication profile were selected and operationalized. Results revealed that televiwers belonged to high socio-economic strata as per the classification of National Council of Applied Economic Research as their average annual income was Rs. 2,26,458 with saving in banks and insurance policies. Most viewers were males and belonged to middle age group having joint as well as nuclear family with most having at least primary level education with average fisheries experience of 12.8 years. They had land holding in the range of 2-4 ha and had pond of their own or on lease. Test for significance of correlation coefficient of selected socio-economic variables was done using SPSS version 16.0 and hypothesis tested was whether the value of correlation coefficient is large enough to indicate that there is a significant relationship between the variables. Income was found to be negatively correlated with education and cosmopoliteness and the difference was found to be significant. As regards to communication profile, all viewers owned television set, with maximum having Direct to Home connection and more that 80% having mobile phones. All of them had an exposure to fisheries-agriculture based television programmes, i.e., Krishidarshan and Annadata, telecast by both public and private channels. Electricity was available at all households. However, in event of failure of electricity, battery and solar panels were used. Socio-economic and communication profile of televiewersÂ of farm based programmes can be used for making effective and attractive programmes and this information can be used by advertisement companies also. Â Key words: Socio-economic, fisheries, televiewers, television, programmes.